Four new South African monotypic grass-feeding leafhopper genera and a revision of Lecacis (Hemiptera, Cicadomorpha, Cicadellidae) - Stiller, Michael (Zootaxa, 2011)
Four new monotypic leafhopper genera in Deltocephalinae and their type species are described: Ochromelanus brachyphallus gen.n. & sp.n. (Deltocephalini), Teinopterus microphallus gen.n. & sp.n. (Paralimnini), Tytthuspilus onychophallus gen.n. & sp.n. (Paralimnini) and Umeqi okhahlamba gen.n. & sp.n. (Paralimnini). These genera and species are associated with grass mainly in the Fynbos and Grassland Biomes of South Africa. The revision of Lecacis Theron (Paralimnini) concerns the redescription of the male type species of L. platypennis, the new description of the female, and two new species. Lecacis species appear to be distributed somewhat randomly in the Grassland and Savanna Biome of South Africa.